PENGARUH SUSTAINABILITY REPORTING, INTELLECTUAL CAPITAL, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Nisrina Nabilah; Fachrurrozie Fachrurrozie (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the influence of sustainability reporting, intellectual capital, and capital structure on firm value, with good corporate governance as a moderating variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The research method used was quantitative with purposive sampling, resulting in 140 observations. The research data were secondary data obtained from annual reports and corporate sustainability reports. These data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) using EViews SV 12. The results showed that sustainability reporting, intellectual capital, and capital structure had no significant effect on firm value. Furthermore, good corporate governance was unable to moderate the effect of sustainability reporting and intellectual capital on firm value. However, good corporate governance significantly strengthened the influence of capital structure on firm value. The conclusion of this study indicates that sustainability reporting, intellectual capital, and capital structure are not yet the primary determinants of firm value. However, effective implementation of good corporate governance can strengthen the relationship between capital structure and firm value by improving oversight and control of corporate financing policies. Keywords: Sustainability Reporting, Intellectual Capital, Capital Structure, Good Corporate Governance, Company Value